Study of Hydrodynamic Dispersion Laws in Homogeneous and Heterogeneous Soil - WANG Da; ZHUANG Luwen; LIN Kairong; FENG Shangchao (Renmin Zhujiang)
To investigate the general laws of solute transport in homogeneous and heterogeneous soil,this study conducts column experiments in the laboratory to observe and monitor hydrodynamic dispersion under different conditions.The measured breakthrough curves of solute are fitted and analyzed by the classical advection-diffusion equation (ADE).The results reveal that the solute concentration has little effect on the hydrodynamic diffusion coefficient in homogeneous soil;however,the flow rate of solute transport can promote hydrodynamic diffusion,namely that a higher flow rate can lead to a larger hydrodynamic diffusion coefficient,and the breakthrough curves can be completed faster.There is a positive correlation between the hydrodynamic diffusion coefficient and the mean particle size of the sand at a certain flow rate.In addition,the scale effect is prominent in the solute transport process in soil;generally,the hydrodynamic diffusion coefficient increases with the traveling distance.Compared with the case of homogeneous soil,the heterogeneity and different layered structures of layered soil have a more significant influence on hydrodynamic dispersion.